2013
DOI: 10.4103/0973-8258.111600
|View full text |Cite
|
Sign up to set email alerts
|

Neuro beneficial effects of Pimpinella anisum against lead exposure

Abstract: Background:The essential oil of Pimpinella anisum has been widely used in traditional medicine to treat a variety of diseases, including some neurological disorders. Aims: This study was aimed to test, in vivo, the possible anxiolytic and antidepressant effects, of the essential oil of Pimpinella anisum against chronic lead acetate (0.2%) intoxication during the gestation and lactation period, in Wistar rat pups. Settings and Design: Wistar rat pups were exposed to lead via their dams' drinking water from post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
3
10
1
Order By: Relevance
“…This effect is due mainly to the direct action of lead on serotoninergic and glutamatergic transmission in brain and its receptors respectively: 5HT1A and NMDA which are involved in the physiopathology of depression [27], [28].Anxiety caused by lead acetate was also confirmed through Dark and light test. Hence, our results were in agreement with the finding of [8].However, this effect can be explained by the interaction of lead with serotoninergic and dopaminergic neurons in Hippocampus. This system seems to be involved in the regulation of CRF (Corticotropin Releasing Factor) which play a key role in anxiety behavior.…”
Section: Forced Swimming Test (Fst) and Dark /Light Test (Dlt)supporting
confidence: 93%
See 2 more Smart Citations
“…This effect is due mainly to the direct action of lead on serotoninergic and glutamatergic transmission in brain and its receptors respectively: 5HT1A and NMDA which are involved in the physiopathology of depression [27], [28].Anxiety caused by lead acetate was also confirmed through Dark and light test. Hence, our results were in agreement with the finding of [8].However, this effect can be explained by the interaction of lead with serotoninergic and dopaminergic neurons in Hippocampus. This system seems to be involved in the regulation of CRF (Corticotropin Releasing Factor) which play a key role in anxiety behavior.…”
Section: Forced Swimming Test (Fst) and Dark /Light Test (Dlt)supporting
confidence: 93%
“…The current finding showed that exposure to lead during gestation and lactation affected the locomotor activity in the Open Filed test. Further, lead caused a significant hyperactivity, which was in accordance with lot of studies [8], [22]. Many suggestions have been proposed to explain this effect, some of this relied the change in the open field behavior to the alteration of dopaminergic, serotonergic and cholinergic systems [14].…”
Section: Open Field (Of)supporting
confidence: 84%
See 1 more Smart Citation
“…After conducting behavioral tests, the study rats were sacrificed in the morning; blood was collected from portal vein in tubes, then used to determine the blood glucose level by a glucometer (Kahloula et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Stillness therefore reflects the state of resignation that can be associated with "despair". The test duration is 6 min (Kahloula et al, 2013;Elizalde et al, 2008).…”
Section: Forced Swimming Testmentioning
confidence: 99%